Respuesta :

leena

Hey there! :)

Answer:

x = -4/3, 0, 4.

Step-by-step explanation:

Starting with:

6x³ - 16x² - 32x = 0

Factor out the greatest common factor between each term, or 2x:

2x(3x² - 8x - 16) = 0

Factor the expression inside the parenthesis:

2x(3x +4)(x - 4) = 0

Use the Zero Product Property to solve the equation:

2x = 0

x = 0

---------

3x + 4 = 0

3x = -4

x = -4/3

-------------

x - 4 = 0

x = 4

-------------

Therefore, the solutions to this equation are:

x = -4/3, 0, 4.

Answer:

Step-by-step explanation:

The common factor is 2x

2x(3x^2 - 8x - 16)

(x - 4)(3x+4)*2x = 0

x = 2

x = 4

x = -4/3

This does not graph too awfully well, but at least it givens you a notion of the roots.

Ver imagen jcherry99